2021
DOI: 10.1037/hum0000256
|View full text |Cite
|
Sign up to set email alerts
|

In the company of animals: Accompaniment transforms prisoners into colleagues, teachers, and healers.

Abstract: The setting is a high-security state prison inhabited by over 2,300 men labeled as "violent," often having decades before access to the privilege of parole. Over 400 of these men have life without parole. This particular prison is surrounded by a national forest. We begin by describing current problems in corrections to introduce the difficulties facing not only these prisoners themselves, but also the psychologists tasked with rehabilitating them. A serendipitous discovery found that photographs of dogs and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 38 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…It is necessary to provide empathy and compassion to heal the traumatized (Schore, 2019). In over 8 years’ experience working with men who were considered to be the most violent in a statewide prison population, we found that providing a trustworthy presence via attachment-based psychotherapy (Costello, 2013) and accompaniment (Watkins, 2015), while embedded in a nature-based culture, was effective in transforming prisoners (Bloom et al, 2021; Bradshaw & Bloom, 2020). Therefore, it appears that the problem in corrections is the delivery of rehabilitative content, and not the content itself.…”
Section: Attachment Accompaniment and Nature As Alternatives To Punis...mentioning
confidence: 99%
See 2 more Smart Citations
“…It is necessary to provide empathy and compassion to heal the traumatized (Schore, 2019). In over 8 years’ experience working with men who were considered to be the most violent in a statewide prison population, we found that providing a trustworthy presence via attachment-based psychotherapy (Costello, 2013) and accompaniment (Watkins, 2015), while embedded in a nature-based culture, was effective in transforming prisoners (Bloom et al, 2021; Bradshaw & Bloom, 2020). Therefore, it appears that the problem in corrections is the delivery of rehabilitative content, and not the content itself.…”
Section: Attachment Accompaniment and Nature As Alternatives To Punis...mentioning
confidence: 99%
“…Such catastrophic failures in other public sectors would trigger rigorous problem analysis and reassessment, resulting in subsequent demands for alternative approaches (Whitely et al, 2014). When viewed through the lens of psychological theory and data, the source of failure in prison rehabilitation efforts unveils (Bloom et al, 2021; Bradshaw & Bloom, 2020; Garbarino, 2017; Roach, 2013).…”
Section: A Culture Of Punishmentmentioning
confidence: 99%
See 1 more Smart Citation
“…One prisoner began to draw elephants to share during groups (see Appendix). He has also coauthored an article with us in which some of his stories are presented (Bloom et al, 2020).…”
Section: Elephants In the Forestmentioning
confidence: 99%
“…Another prisoner with a 30-year maximum (15-year minimum) sentence wrote nature-based materials for group programs. His rendering of the animal accounts, told from the animal’s perspectives, helped prisoners develop empathy for others (Bloom et al, 2020). This nature- and attachment-based, trauma-informed approach effectively transformed prisoners into collaborating colleagues.…”
Section: Elephants In the Forestmentioning
confidence: 99%